STRENGTHENING STUDENTS' RELIGIOUS CHARACTER THROUGH RELIGIOUS PRACTICES IN ELEMENTARY SCHOOL - Laurita Nurmila Arinda; Muhlasin Amrullah; Khizanatul Hikmah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper describes the strengthening of students' religious character education through religious practices at Al-Islam Plus Krian Elementary School. The research uses qualitative research with a phenomenological approach. The data collection methods used are observation, interviews, and documentation. Data analysis used in the research is data reduction, data presentation, and conclusion. Data validity testing used in the research is triangulation techniques, namely source and technique triangulations. The research results entitled Strengthening Students’ Religious Character through Religious Practices in Elementary School, which consist of religious activities, are the 7S culture, praying before and after learning, reciting hadiths and daily prayers, reciting the Quran, reading asmaul husna, istighosah, praying in congregations (duha, zuhr, asar, Friday), tarjamah, tahfidz Al-Qur'an, and PHBI. The impact of religious practices instilled in Al-Islam Plus Krian Elementary School indicates a significant impact for each student, which can increase students’ understanding and a better understanding related to the benefits of the positive activities they do and will be applied by them in their daily activities in accordance with the Shariah of Islam.